Feasibility of precompetition medical assessment at FIFA World Cups for female youth players - Dvorak, J.; Grimm, K.; Schmied, C.; Junge, A. (British Journal of Sports Medicine, 2012)
Background Although most experts agree that preparticipation screening is important to prevent sudden cardiac death in sport, only a few reports have been published on the feasibility of its practical implementation.Methods The football associations participating in the U-17 and U-20 Women's World Cups 2010 were asked to perform a standardised precompetition medical assessment (PCMA) of their players (in total 672).Results Compliance with the requirement for performing the PCMA was high among all teams, particularly from African, Asian and Central/South American countries. No relevant abnormal findings in personal history and clinical cardiological examination were reported. Athletic ECG patterns were frequent, but very few findings were considered to require further investigation. All players were declared as eligible to play.Conclusions Based on the demonstrated feasibility of performing a comprehensive PCMA in elite female youth players, the Fédération Internationale de Football Association (FIFA) Executive Committee decided to make the PCMA a compulsory requirement for all FIFA competitions.